Do formula-based intergovernmental transfer mechanisms eliminate politically motivated targeting? Evidence from Ghana - Banful, Afua Branoah (International Food Policy Research Institute, 2010)
Theories of fiscal federalism imply that determining intergovernmental transfers based on the political incentives results in inefficient allocation of resources across geographic regions. Such practices also can result in tensions between classes, and ethnic and religious groups, which are concentrated in distinct geographical areas. Nevertheless, empirical evidence consistently confirms that the practice of allocating government resources based on political relationships continues to be pervasive around the world. This brief summarizes the results of an IFPRI study in Ghana assessing the effectiveness of formulas as a strategy to limit political motivation behind resource sharing.